2022
DOI: 10.21203/rs.3.rs-2131027/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The additional unique ability of TuMV HC-Pro in inhibiting HEN1 activity for enhancing the autophagic AGO1 degradation in RNA silencing suppression

Abstract: Genomes of potyviruses, the largest group of plant viruses, encode HC-Pro proteins that mediate RNA silencing suppression. HC-Pros may exhibit only 40% similarity between species, and induce different levels in autophagic ARGONAUTE1 (AGO1) degradation. Our data indicated that HC-Pro of turnip mosaic virus (HC-ProTu) could efficiently trigger AGO1 degradation through autophagy compared with HC-Pros of zucchini yellow mosaic virus (HC-ProZy) and tobacco etch virus (HC-ProTe). Furthermore, HC-ProTu, but not in HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 41 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…3e). Furthermore, Wei et al (2022) and Shang (2020) demonstrated that P1/HC-Pro Tu /atg8a ge plants, which have an ATG8a knockout mutant, have recovered AGO1 levels. Surprisingly, the normalized in vitro RISC activity returned to 20% and 39% e ciency at 10 ng and 20 ng, respectively, in P1/HC-Pro Tu /atg8a ge plants, suggesting restoration of RISC regulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3e). Furthermore, Wei et al (2022) and Shang (2020) demonstrated that P1/HC-Pro Tu /atg8a ge plants, which have an ATG8a knockout mutant, have recovered AGO1 levels. Surprisingly, the normalized in vitro RISC activity returned to 20% and 39% e ciency at 10 ng and 20 ng, respectively, in P1/HC-Pro Tu /atg8a ge plants, suggesting restoration of RISC regulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we can apply the same approach to generate AGO2-speci c antibodies for AGO2-IP and in vitro RISC assays in comparative studies. Hu et al (2020) and Wei et al (2022) demonstrated that HC-Pro Tu has more e cient to trigger autophagic AGO1 degradation than other HC-Pro. AGO1 degradation was also observed in TuGR-infected Arabidopsis, suggesting that HC-Pro Tu -mediated AGO1 degradation is one approach for gene silencing suppression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations